Class II malocclusion treatment using combined Twin Block and fixed orthodontic appliances – A case report - Saud A. Al-Anezi (Saudi Dental Journal)
The effect of the Twin Block functional orthodontic appliances is mostly dento-alveolar with small skeletal effect. There are certain clinical indications where functional appliances can be used successfully in class II malocclusion e.g. in a growing patient. The use of these appliances is greatly dependent on the patient’s compliance and they simplify the fixed appliance phase. In this case, a 13-year old adolescent was treated with Twin Block appliance followed by fixed appliance to detail the occlusion. The design and treatment effects were demonstrated in this case report. Keywords: Class II malocclusion, Twin Block appliance, Case report